Quail Production: A profitable business - Goswami, Durga Shankar; Choudhary, Jagdish Lal; Jat, Jeewan Ram (Indian Farming, 2022)
In the past decade, commercial quail production witnessed tremendous growth in our country and became viable alternate farming due to their delicious meat and rich nutritive value. During this period, a number of breeding-cum-commercial quail units were established dealing with the production of specialized meat and egg type strains to meet the needs of quail growers. This study tries to overcome the major constraints of quail farming by addressing the best management practices, and disease prevention strategies for quail farming.